Early-onset Alzheimer’s disease patient with prion (PRNP) p.Val180Ile mutation - Bagyinszky, Eva (Neuropsychiatr Dis Treat, 2019)
Background: In this study, a known PRNP mutation, Val180Ile (c.G538A), was reported in a 58 years old female patient, clinically diagnosed with Alzheimer’s disease (AD). Case report: The patient presented slowly progressive cognitive decline in memory and visuospatial domain. Neuroimaging showed hippocampal atrophy in MRI and mild amyloid positivity in PET scan. Even though her cerebrospinal fluid (CSF) was positive for 14–3-3 protein, no sign of Creutzfeldt-Jakob diseases symptoms was observed. In addition, reduced Aβ42 and elevated total-Tau and phospho-Tau in CSF also proved the AD diagnosis. The mutation may disturb the hydrophobic core of prion protein, and result in abnormal intramolecular interactions. Due to 23andMe, PRNP Val180Ile could not be categorized either as a mutation with complete penetrance, or as neutral variant, and could have a possible role in neurodegeneration. Pathological overlap was observed between prion diseases and other neurodegenerative diseases, including AD or frontotemporal dementia. Conclusion: Whole exome sequencing and pathway analysis of patient revealed rare or possible risk variants in AD associated genes, such as SORL1 or ABCA7. Along with PRNP, AD risk genes may play a role in negative regulation of amyloid formation. Dysfunctions in these genes could possibly be associated in reduced neuroprotection and amyloid clearance.